ABOUT METHOD FOR CONTINUOUS BEAM ACCOUNT - A. Ch. Yakubovsky; Ch. A. Yakubovsky (Наука и техника, 2006)
The paper considers in detail a calculation of a multispan continuous beam using two methods: work method and method of three-moment equations. As a result of comparison and detailed analysis of these methods it has been exhibited that the calculation using three-moment equations is non effective and awkward method. It is known that the method for calculation of continuous beam using three-moment equations is only artificial transformation of work method. Thus while calculating any statically indeterminate systems including continuous beams it is more expedient to apply a common calculative method, that is a work method.